Feasibility and safety of tailored dosing schedule for eculizumab based on therapeutic drug monitoring: Lessons from a prospective multicentric study. Issue 5 (7th December 2020) - Passot, Christophe; Sberro‐Soussan, Rebecca; Bertrand, Dominique; Caillard, Sophie; Schvartz, Betoul; Domenger, Camille; Contin‐Bordes, Cécile; Paintaud, Gilles; Halimi, Jean‐Michel; Ternant, David; Gatault, Philippe
Abstract : Aims: Eculizumab is an anti‐C5 monoclonal antibody approved for rare diseases including atypical haemolytic–uraemic syndrome. The maintenance phase dosing regimen is identical for all adult patients: 1200 mg every 2 weeks. Recent studies reported an overexposure in many patients when considering a target trough concentration range of 50–100 mg/L. The aim of the present work was to validate the feasibility of therapeutic drug monitoring of eculizumab in atypical haemolytic–uraemic syndrome patients. Methods: We performed a 2‐step prospective multicentre study. In the first phase, we developed a pharmacokinetic population model using data from 40 patients and identified patients for whom a 1‐week lengthening of interval between infusions would lead to a trough concentration above 100 mg/L. In the second phase, selected patients were allocated a 1‐week extension and eculizumab trough concentrations were monitored. Results: The model confirmed the previously reported influence of bodyweight on elimination clearance and predicted that 36 (90%) patients would be eligible for interval extension. In the second phase of the study, a 1‐week lengthening of interval between infusions was performed in 15 patients whose trough concentration at the next visit was predicted with a Bayesian model to be above 100 mg/L. After interval extension, 10 patients (67%) presented measured trough concentrations over 100 mg/L. No biological or clinical recurrence of disease was observed, even in the 5 patients with concentrations below 100 mg/L in whom the initial dosing regimen was resumed. Conclusion: Safe eculizumab interval adjustment is feasible with a PK monitoring.